2021
DOI: 10.1155/2021/9966000
|View full text |Cite
|
Sign up to set email alerts
|

The SP/NK1R System-Mediated ROS Generation in GBM Cells through Inhibiting Glutaredoxin Protein

Abstract: Altered redox balance is among the main contributing factors developing glioblastoma multiforme (GBM), a highly aggressive grade IV brain tumor. Neuropeptide substance P (SP) plays a key role in modifying the cellular redox environment by activating the neurokinin-1 receptor (NK1R). In this study, we aimed to investigate the redox-modulating properties of both SP and a commercially available NK1R antagonist, aprepitant in GBM cells. To detect the effect of aprepitant on the viability of U87 glioblastoma cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…40 In this study, we confirmed that envZ/ompR affects desiccation tolerance by downregulating the maltodextrin-binding protein and influences protein oxidative stress by downregulating grxC. Glutaredoxin, found in both eukaryotes (such as GBM cells) 41 and prokaryotes (such as bifidobacteria), 42 is a conserved protein that maintains cellular redox balance. The maltodextrinbinding protein can protect the molecular structure of C. sakazakii under desiccation by binding maltodextrin.…”
Section: ■ Discussionsupporting
confidence: 71%
“…40 In this study, we confirmed that envZ/ompR affects desiccation tolerance by downregulating the maltodextrin-binding protein and influences protein oxidative stress by downregulating grxC. Glutaredoxin, found in both eukaryotes (such as GBM cells) 41 and prokaryotes (such as bifidobacteria), 42 is a conserved protein that maintains cellular redox balance. The maltodextrinbinding protein can protect the molecular structure of C. sakazakii under desiccation by binding maltodextrin.…”
Section: ■ Discussionsupporting
confidence: 71%
“…Immune checkpoints are potent antioxidant regulators that control cellular tolerance and prevent tumors. Immune checkpoints assist the immune system in response to infections and cancer, which may protect tissues from damage ( 11 - 13 ). The concept that the immune system might restrict tumor development and cancer, dates back to 1893, when William Cooley used live bacteria as an immunological stimulant to treat cancer patients ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpressed NK1R is related to glioblastoma multiforme (GBM). NK1R-mediating in ammation release reactive oxygen species (ROS) through inhibiting expression and enzymatic activity of glutaredoxin in GBM, which promotes tumorigenesis by mutagenic effects 15,16 . Contrarily, NK1R downregulation is related to breast cancer 17 .…”
Section: Introductionmentioning
confidence: 99%